L-Glutamine Supplementation Alleviates Constipation during Late Gestation of Mini Sows by Modifying the Microbiota Composition in Feces - Zhang, Yuanyuan (Biomed Res Int, 2017)
Constipation occurs frequently in both sows and humans, particularly, during late gestation. The microbial community of the porcine gut, the enteric microbiota, plays a critical role in functions that sustain intestinal health. Hence, microbial regulation during pregnancy may be important to prevent host constipation. The present study was conducted to determine whether L-glutamine (Gln) supplementation improved intestinal function and alleviated constipation by regulation of enteric microbiota. 16S rRNA sequences obtained from fecal samples from 9 constipated sows (3 in the constipation group and 6 in the 1.0% Gln group) were assessed from gestational day 70 to 84. Comparative analysis showed that the abundance of intestinal-friendly microbiota, that is, Bacteroidetes (P = 0.007) and Actinobacteria (P = 0.037), was comparatively increased in the 1.0% Gln group, while the abundance of pernicious bacteria, Oscillospira (P < 0.001) and Treponema (P = 0.011), was decreased. Dietary supplementation with 1.0% Gln may ameliorate constipation of sows by regulated endogenous gut microbiota.